2013
DOI: 10.1155/2013/631479
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristics of Abuse Experiences and Depression Symptoms among Injection Drug-Using Female Sex Workers in Mexico

Abstract: This mixed methods study examined the prevalence and characteristics of physical and sexual abuse and depression symptoms among 624 injection drug-using female sex workers (FSW-IDUs) in Tijuana and Ciudad Juarez, Mexico; a subset of 47 from Tijuana also underwent qualitative interviews. Linear regressions identified correlates of current depression symptoms. In the interviews, FSW-IDUs identified drug use as a method of coping with the trauma they experienced from abuse that occurred before and after age 18 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
70
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 49 publications
(53 reference statements)
5
70
1
2
Order By: Relevance
“…“Psychological distress,” “serious mental illness,” and “psychological problems” are general terms usually comprised of any combination of anxiety, depression, and posttraumatic stress disorder symptoms making comparisons of mental health status across FSW studies difficult. This study examined depression symptoms specifically given the consistently high rates of depression symptoms documented among FSW populations (33, 35, 37, 40, 41). …”
Section: Introductionmentioning
confidence: 99%
“…“Psychological distress,” “serious mental illness,” and “psychological problems” are general terms usually comprised of any combination of anxiety, depression, and posttraumatic stress disorder symptoms making comparisons of mental health status across FSW studies difficult. This study examined depression symptoms specifically given the consistently high rates of depression symptoms documented among FSW populations (33, 35, 37, 40, 41). …”
Section: Introductionmentioning
confidence: 99%
“…35 36 Women-only trauma-informed programmes designed to reduce levels of drug use have had inconclusive results,46 47 though some have suggested that certain subgroups48 49 such as sex workers,50 may benefit from this approach. Our findings are in keeping with theory suggesting that drug use is a strategy to avoid traumatic symptoms 51.…”
Section: Discussionmentioning
confidence: 99%
“…34 Poor mental health has been implicated in SSWs' poor outcomes from drug treatment services 33. Experience of abuse and violence from young age35 36 something frequently reported by SSWs,37 has also been linked to poor treatment outcomes in women 38…”
Section: Introductionmentioning
confidence: 99%
“…El estudio de la salud mental en este grupo se ha abordado de manera escasa en el mundo y en México es casi inexistente, destacando el de Ulibarri et al, 14 realizado en 2010 en sexoservidoras de Tijuana y Ciudad Juárez, en el que describieron las características y la prevalencia del abuso sexual y físico, y su asociación con los síntomas de la depresión.…”
Section: Discussionunclassified